Variation in performance of electronic cattle ear tags and readers - A.M. Bryant; B.B. Barnhardt; M.P. Epp; S.J. Glaenzer; Dale A. Blasi (Kansas Agricultural Experiment Station Research Reports, 2006)
This study was conducted to evaluate the performance of ISO 11785 radio frequency identification (RFID) cattle ear tags and readers under ideal laboratory conditions. Tag and reader manufacturer identities are masked to prevent unintentional conclusions being drawn about any particular tag or reader at this stage of the U.S. National Animal Identification System (US-NAIS) proposed plan. Eight commercially available tag designs were evaluated, and included the half-duplex and full-duplex air interface technologies. Performance parameters of interest for tags were tensile strength, tampering evidence characteristics, as well as the average reading range. Three fixed-antenna stationary readers were used to determine the variability between reading ranges of each reader. Tensile strength parameters differed among tag designs. Only one tag design did not display tamper-evident characteristics. Average reading ranges differed among all eight tag designs, and there were significant differences in performance ranges among the three readers. Performance variation in tags and readers exists due to differences in material makeup (die and copper) and design characteristics. The results of this study support the need for minimum performance standards for ISO 11785 RFID technology as it applies to the US-NAIS.
Keywords: Cattlemen' s Day; 2006; Kansas Agricultural Experiment Station contribution; no. 06-205-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 959; Beef; Performance; Electronic ear tags and readers